Pleiotropic effects of interleukin-6 in a “two-hit” murine model of acute respiratory distress syndrome - Goldman, Julia L. (University of Chicago Press, 2014)
Abstract. Patients with acute respiratory distress syndrome (ARDS) exhibit elevated levels of interleukin-6 (IL-6), which correlate with increased morbidity and mortality. The exact role of IL-6 in ARDS has proven difficult to study because it exhibits either pro- or anti-inflammatory actions in mouse models of lung injury, depending on the model utilized. In order to improve understanding of the role of this complex cytokine in ARDS, we evaluated IL-6 using the clinically relevant combination of lipopolysaccharide (LPS) and ventilator-induced lung injury (VILI) in IL-6(−/−) mice. Bronchoalveolar lavage fluid (BAL), whole-lung tissue, and histology were evaluated for inflammatory markers of injury. Transendothelial electrical resistance was used to evaluate the action of IL-6 on endothelial cells in vitro. In wild-type mice, the combination model showed a significant increase in lung injury compared to either LPS or VILI alone. IL-6(−/−) mice exhibited a statistically significant decrease in BAL cellular inflammation as well as lower histologic scores for lung injury, changes observed only in the combination model. A paradoxical increase in BAL total protein was observed in IL-6(−/−) mice exposed to LPS, suggesting that IL-6 provides protection from vascular leakage. However, in vitro data showed that IL-6, when combined with its soluble receptor, actually caused a significant increase in endothelial cell permeability, suggesting that the protection seen in vivo was likely due to complex interactions of IL-6 and other inflammatory mediators rather than to direct effects of IL-6. These studies suggest that a dual-injury model exhibits utility in evaluating the pleiotropic effects of IL-6 in ARDS on inflammatory cells and lung endothelium.